From Field to Functional Food Integrating Microbial Innovation and Agroindustry Development for Sustainable Agriculture - Bangkele, Lisa Indriani; Aksarah, Aris; Arfan; Zainal (Professorline, 2025)
Sustainable agricultural development increasingly depends on innovations that bridge biological productivity at the farm level and value creation within agroindustry. This study proposes an integrated framework connecting microbial bioinnovation in crop production with functional food development, forming a “Field-to-Functional-Food” model. The research employs a conceptual synthesis based on two empirical datasets from experimental studies on microbial consortia (Fm48 and R15) applied to rice cultivation and on instant ginger drink formulations as a value-added agroindustrial product. The microbial consortium demonstrated significant improvements in rice yield components productive tillers, panicle length, and 1000-grain weight through enhanced nutrient uptake and reduced chemical input dependency. Meanwhile, the functional food study showed that the addition of 15% milk powder increased protein content and antioxidant activity in instant ginger products, improving both nutritional value and consumer acceptance. By integrating these findings, the proposed framework illustrates how upstream microbial innovation can serve as the biological foundation for downstream agroindustrial transformation. This integration promotes a circular and sustainable agrocomplex system characterized by resource efficiency, environmental responsibility, and inclusive economic participation. The conceptual model aligns with the principles of the Blue–Green Economy, emphasizing synergy between biotechnology, processing innovation, and sustainable food systems. The study concludes that linking microbial-based production and functional food processing can enhance agricultural competitiveness, strengthen rural industries, and advance the transition toward an innovative-driven and nutritionally oriented agro-economy